Fi : a memoir - Fuller, Alexandra, 1969- (Grove Press, 2024)
"From the award-winning New York Times-bestselling author, Alexandra Fuller, comes a career defining memoir about grieving the sudden loss of her twenty-one-year-old child. "Fair to say, I was in a ribald state the summer before my fiftieth birthday." And so begins Alexandra Fuller's open, vivid new memoir, Fi. It's midsummer in Wyoming and Alexandra is barely hanging on. Grieving her father and pining for her home country of Zimbabwe, reeling from a midlife breakup, freshly sober and piecing her way uncertainly through a volatile new relationship with a younger woman, Alexandra vows to get herself back on even keel. And then--suddenly and incomprehensibly--her son Fi, at twenty-one years old, dies in his sleep. No stranger to loss--young siblings, a parent, a home country--Alexandra is nonetheless leveled. At the same time, she is painfully aware that she cannot succumb and abandon her two surviving daughters as her mother before her had done. From a sheep wagon deep in the mountains of Wyoming to a grief sanctuary in New Mexico to a silent meditation retreat in Alberta, Canada, Alexandra journeys up and down the spine of the Rocky Mountains in an attempt to find how to grieve herself whole. There is no answer, and there are countless answers--in poetry, in rituals and routines, in nature and in the indigenous wisdom she absorbed as a child in Zimbabwe. By turns disarming, devastating and unexpectedly, blessedly funny, Alexandra recounts the wild medicine of painstakingly grieving a child in a culture that has no instructions for it"--